Potato crop growth as affected by nitrogen and plant density - Oliveira, Carlos Alberto da Silva (Pesquisa Agropecuaria Brasileira, 2000)
Growth and development variables and dry matter characteristics were studied for cultivar Snowden of potato (Solanum tuberosum L.) to evaluate nitrogen and plant density influence. Disregarding ending of season plant stress, the average number of actives haulms per plant was five and it was not affected by plant spacing. However, seasonal and final number of active haulms per plant were increased at 200 kg/ha of nitrogen. Maximum stem elongation was reached quickly with double density and had the tendency to keep constant at the highest and lowest nitrogen levels after 70 days after planting. Specific stem mass defined as mass per unit stem length was established as an indirect measure of stem thickness and load capacity. Specific leaf mass position in plant was higher at upper stem leaves, increased as plant density increased and did not vary markedly over time throughout the season. The rate of leaf appearance increased drastically due to more branching caused by high nitrogen level, and increased above ground dry matter per plant. Canopy growth and development influenced main tuber yield components. The number of active tubers per haulm decreased after 60 days after planting showing that tuberization is reversible. Tuber growth functions were established allowing the estimate of dry biomass partitioning coefficients for each plant organ.